2013
DOI: 10.1108/17579881311302365
|View full text |Cite
|
Sign up to set email alerts
|

Mobile applications in the hospitality industry

Abstract: PurposeThe purpose of this study is to examine customer intentions to download mobile applications in the hospitality industry. Even though major hospitality companies offer the mobile applications, many customers have not utilized them. The results showed what encouraged customers to download mobile applications in the hospitality industry.Design/methodology/approachThe Technology Acceptance Model was applied for this research to explain customer intentions. College students were the target population of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 17 publications
4
49
0
1
Order By: Relevance
“…The overall average age of the respondents is 26.1 years old, 42% of respondents are male while 58% are female, as shown in Table 1. This is comparable to the description of the sample population in Mo Kwon, Bae, and Blum (2013), in that respondents are younger, as anticipated in the app user profile. On average, these respondents have 36 apps on their smartphones, but only 4.9 are specifically hospitality or travel apps.…”
Section: Participant Profilesupporting
confidence: 67%
See 1 more Smart Citation
“…The overall average age of the respondents is 26.1 years old, 42% of respondents are male while 58% are female, as shown in Table 1. This is comparable to the description of the sample population in Mo Kwon, Bae, and Blum (2013), in that respondents are younger, as anticipated in the app user profile. On average, these respondents have 36 apps on their smartphones, but only 4.9 are specifically hospitality or travel apps.…”
Section: Participant Profilesupporting
confidence: 67%
“…Another limitation was the sample size with 214 responses who have installed one or more hospitality and travel apps, but only 57 had used hotel apps before. Mo Kwon et al (2013) report that most hospitality app users had used airline apps (70%) or restaurant apps (17%), but not hotel apps and Wang et al (2015) analysed 5878 OTAs and hotels app reviews and reveal that only 1613 reviews (27%) are related to hotels while the rest are related to OTAs. This may indicate that customers are not yet ready for hotel specific apps.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…They found that it was significant in predicting mobile ticketing adoption [11]. Cheng and Huang investigated high speed rail passengers' acceptance of mobile ticketing services and results indicated that a combination of the mental accounting theory and TAM was appropriate for explaining passengers' mobile ticketing service adoption [12]. A detailed literature review indicated that there were quite a few studies on the adoption of mobile travel booking from the travel standpoint.…”
Section: Mobile Bookingmentioning
confidence: 99%
“…Existing studies of mobile devices and apps in the tourism context have mainly focused on the strategic importance and impacts of mobile technology on the tourists' experience (Neuhofer et al, 2012;Tjostheim and Fesenmaier, 2008;Wang et al, 2014Wang et al, , 2016, and on mobile technology use intention based on the Technology Acceptance Model (TAM) and its derivatives (Hsu and Chu, 2014; Kim et al,2008;Kwon et al, 2013;Rivera et al, 2015 ). While these studies have advanced the body of knowledge of tourism mobile technology, they might not be able to identify specific task and technology characteristics at the early, beginning stage of designing a tourist-preferred app.…”
Section: Introductionmentioning
confidence: 99%